Cervical cancer screening delay and associated factors among women with HIV in Lesotho: a mixed-methods study - Michelle T. Harder; Moliehi Mokete; Frédérique Chammartin; Malebanye Lerotholi; Lipontso Motaboli; Mathebe Kopo; Mpho Kao; Moleboheng Mokebe; Ntoiseng Chejane; Palesa Mahlatsi; Morongoe Nyakane; Tapiwa Tarumbiswa; et al. (BMC, 2024)
Abstract Background Cervical cancer is the fourth most common cancer in women worldwide, and women with human immunodeficiency virus (HIV) are particularly at risk of developing it. Regular screening effectively prevents morbidity and mortality. This mixed-methods study quantitatively assessed cervical cancer screening uptake and qualitatively explored the process of undergoing cervical cancer screening to understand possible reasons for delayed screening among women with HIV in Lesotho. Methods Between October 2020 and March 2022, the Viral load Triggered ART care in Lesotho (VITAL) trial enrolled women aged 18 years and older with HIV who were taking antiretroviral therapy (ART). Cervical cancer screening delay was defined as reporting a screening that occurred more than two years ago or never having been screened. Cervical cancer screening uptake and the association between screening delay and sociodemographic variables were assessed using a multivariable mixed-effects logistic regression model accounting for clustering at clinic level. In-depth interviews were conducted with 16 women to obtain information on awareness, perceptions, and barriers to cervical cancer screening and were analyzed using thematic analysis. Results Quantitative data were available for 3790 women. Among them, cervical cancer screening was delayed in 1814 (47.9%), including 1533 (40.5%) who were never screened. Compared to women aged 25 to 39 years, women aged 18 to 24 years (adjusted odds ratio (aOR) 2.8; 95% confidence interval (CI) 2.1-3.7), women aged 40 to 59 years (aOR 1.3; CI 1.1-1.6), and women older than 60 years (aOR 3.9; CI 3.0-5.1) were at higher risk of screening delay. Furthermore, time on ART below 6 months (aOR 1.6; CI 1.1-2.3) compared to above 6 months was associated with screening delay. Qualitative data identified limited awareness of cervical cancer risks and screening guidelines, misconceptions and fears created by the influence of other women's narratives, and low internal motivation as the main barriers to screening uptake. Conclusions Cervical cancer screening delay was common. Limited personal awareness and motivation as well as the negative influence of other women were the primary internal barriers to cervical cancer screening. Awareness and screening campaigns in Lesotho should consider these factors. Trial registration clinicaltrials.gov, NCT04527874, August 27, 2020.